Eupatilin: a natural pharmacologically active flavone compound with its wide range applications. Issue 1 (2nd January 2020) - Nageen, Bushra; Sarfraz, Iqra; Rasul, Azhar; Hussain, Ghulam; Rukhsar, Fariha; Irshad, Somia; Riaz, Ammara; Selamoglu, Zeliha; Ali, Muhammad
Abstract: Eupatilin (5, 7-dihydroxy-3′, 4′, 6-trimethoxyflavone) is a pharmacologically active flavone which has been isolated from a variety of medicinal plants. Eupatilin is known to possess various pharmacological properties such as anti-cancer, anti-oxidant, and anti-inflammatory. It is speculated that eupatilin could be subjected to structural optimization for the synthesis of derivative analogs to reinforce its efficacy, to minimize toxicity, and to optimize absorption profiles, which will ultimately lead towards potent drug candidates. Although, reported data acclaim multiple pharmacological activities of eupatilin but further experimentations on its molecular mechanism of action are yet mandatory to elucidate full spectrum of its pharmacological activities. Abstract : UF0001